2020
DOI: 10.1101/2020.06.18.159582
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FHOD-1 is the only formin inCaenorhabditis elegansthat promotes striated muscle growth and Z-line organization in a cell autonomous manner

Abstract: The striated body wall muscles of Caenorhabditis elegans are a simple model system with wellcharacterized sarcomeres that have many vertebrate protein homologs. Previously, we observed deletion mutants for two formin genes, fhod-1 and cyk-1, developed thin muscles with abnormal dense bodies/sarcomere Z-lines. However, the nature of the cyk-1 mutation necessitated maternal CYK-1 expression for viability of the examined animals. Here, we tested the effects of complete loss of CYK-1 using a fast acting temperatur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…We used C. elegans as a simple model to investigate whether formins promote transcription by SRF during striated muscle development in vivo. One advantage to using C. elegans is that FHOD-1 is the only endogenous formin that directly promotes BWM growth or sarcomere formation [41], compared to evidence that at least five formins are essential for myofibrillogenesis in cardiomyocyte cell culture [67]. Consistent with the possibility FHOD-1 and SRF might function in the same pathway in C. elegans, previous studies had independently shown worms bearing a fhod-1(Δ) deletion allele and worms bearing an unc-120(hypo) hypomorphic allele of the worm SRF gene, each exhibit thin BWMs [40,44].…”
Section: Srf Activity Is Not Formin-dependent In Worm Bwmmentioning
confidence: 99%
See 1 more Smart Citation
“…We used C. elegans as a simple model to investigate whether formins promote transcription by SRF during striated muscle development in vivo. One advantage to using C. elegans is that FHOD-1 is the only endogenous formin that directly promotes BWM growth or sarcomere formation [41], compared to evidence that at least five formins are essential for myofibrillogenesis in cardiomyocyte cell culture [67]. Consistent with the possibility FHOD-1 and SRF might function in the same pathway in C. elegans, previous studies had independently shown worms bearing a fhod-1(Δ) deletion allele and worms bearing an unc-120(hypo) hypomorphic allele of the worm SRF gene, each exhibit thin BWMs [40,44].…”
Section: Srf Activity Is Not Formin-dependent In Worm Bwmmentioning
confidence: 99%
“…Worm FHOD-1 is expressed in all muscle types and is the only formin that promotes BWM growth in a cell autonomous manner [40,41]. One advantage to the use of C. elegans as a model system is that absence of FHOD-1 is not lethal, unlike loss of FHOD3 in mice, allowing (which was not certified by peer review) is the author/funder.…”
Section: Introductionmentioning
confidence: 99%
“…Together, these data suggest mDIA1, mDIA2, and FHOD1 contribute to We used C. elegans as a simple model to investigate whether formins promote transcription by SRF during striated muscle development in vivo. One advantage to using C. elegans is that FHOD-1 is the only endogenous formin that directly promotes BWM growth or sarcomere formation [41], compared to evidence that at least five formins are essential for myofibrillogenesis in cardiomyocyte cell culture [67]. Consistent with the possibility FHOD-1 and SRF might function in the same pathway in C. elegans, previous studies had independently shown worms bearing a fhod-1(Δ) deletion allele and worms bearing an unc-120 (hypo) hypomorphic allele of the worm SRF gene, each exhibit thin BWMs [40,44].…”
Section: Srf Activity Is Not Formin-dependent In Worm Bwmmentioning
confidence: 99%
“…Worm FHOD-1 is expressed in all muscle types and is the only formin that promotes BWM growth in a cell autonomous manner [40,41]. One advantage to the use of C. elegans as a model system is that absence of FHOD-1 is not lethal, unlike loss of FHOD3 in mice, allowing investigation of the effects of FHOD-1 loss on striated muscle at later stages of development.…”
Section: Introductionmentioning
confidence: 99%